(untitled) (Ozone Therapy Global Journal, 2011)
There remains much to investigate about the process of maturation and development of the Nervous System, but given the biological properties of ozone, it is supposed to be useful in improving the quality of life of patients with Cerebral Palsy. Due to this, it was decided to perform this pre-experiment with a pre-test and post-test design, with a single group, in the Pediatric Provincial Hospital of Sancti Spiritus in the period of June 2006-December 2009, with the objective of determining the Usefulness of ozone therapy in the treatment of Cerebral Palsy. The population consisted of patients referred to the ozone therapy consultation, and the study group consisted of 43 patients. The variables analyzed were: sleep and feeding pattern, weight gain and clinical response of the immune status. The route of administration was rectal; Concentrations between 15-18-20-25 mcg / ml were used, the volumes varied according to the age and weight of the patient. Cycles of 20 sessions, every 3 months, were completed to complete 4 for one year. Patients were clinically evaluated before and after each cycle. The study group consisted of the largest number in the group of 1 to 5 years. The dependent variables analyzed showed significant improvement at the end of treatment with ozone. Regarding the variability of body weight, the highest percentage was ascending. The group of children under one year presented a better response regarding spasticity. No adverse event was recorded.